Quality of teacher-child relationship and pre-schoolers’ development of self-regulation - Wang, Meihua (2016)
Research suggests that teachers are important agents in children’s development of self-regulation. The purpose of the present study was to explore how teacher-child relationship may influence children’s development of self-regulation, particularly on constructs of emotion regulation and executive functions. 70 preschool children (M = 63.11 months, SD = 0.6, range = 57-70 months; 34 males) were assessed on their performances on two executive function tasks and 21 teachers rated their relationship with the child and child’s display of problem behaviours in the classroom. As hypothesised, teacher-child conflict was positively associated with increased difficulties in self-regulation. Specifically, children who had a conflictual relationship with their teachers were more likely to display difficulties and externalising problems. However, no significant association was found between conflictual teacher-child relationship and children’s display of internalising problems and performance on executive function tasks. Also, no significant association was found for close teacher-child relationship and children’s self-regulatory capabilities. These findings suggest that conflictual teacher-child relationship plays a role in children’s development of self-regulatory abilities. However, the direction of causality cannot be concluded in this study. Future research should extend the findings to a larger sample size and include more measures of executive functions to boost power. Intervention studies targeted at improving the quality of teacher-child relationships could be used to examine direction of causality. This research could inform teachers regarding the importance of having a positive relationship with children under their care and assist early childhood policy-makers in implementing relationship- based training for both pre-schoolers and their teachers.